Problem based learning and intrapersonal intelligence: Effect on the problem-solving ability of human reproductive system material - Irva Faoji Anwar; Rusdi Rusdi; Elsa Lisanti (JURNAL BIOEDUKATIKA, 2021)
Problem Based Learning (PBL) is a learning model that encourages students to solve problems. At the same time, intrapersonal intelligence is a skill needed by students in solving problems so that students can solve problems well. This research aims to determine the effect of the Problem Based Learning (PBL) model and intrapersonal intelligence on high school students' problem-solving skills. The method used was an experiment with a quasi-experimental research type and a 2x2 factorial design—multistage random sampling sample selection technique. All students of class IX reach the population at SMAN 1 Baros. The target population for all class IX of SMAN 1 Baros is 130 students. The research sample consisted of 2 classes IX for the experimental class and two classes IX for the Control class, each of which totaled 65 students. The instrument for the ability to solve problems in the form of description questions consists of 11 items and intrapersonal intelligence in a questionnaire totaling 25 statements. Data analysis and hypothesis testing using two-way ANOVA with the help of the SPSS 21.0 software program. The results showed that the PBL model and intrapersonal intelligence significantly affected problem-solving skills with a sig < 0.05. The data analysis conclusion shows that there is an influence of the PBL model and the intrapersonal intelligence of high school students on the material of the human reproductive system.